النشاط الدعوي للائمة المساجد عبر صفحات التواصل الاجتماعي واثاره على المستخدمين - لعطر الهاشمي عبد الصمد; لعطر مرية أم السعد; د// مساعدي الحسين (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة: جاءت دراستنا بعنوان النشاط الدعوي للائمة المساجد عبر صفحات التواصل الاجتماعي واثاره على المستخدمين- دراسة على عينة مستخدمي مواقع التواصل الاجتماعي وانطلقت دراستنا من الإشكالية: ما أثر النشاط الدعوي عبر صفحات مواقع التواصل الاجتماعي على مستخدميها بولاية الاغواط ؟ وتتفرع الإشكالية العامة للدراسة إلى مجموعة من التساؤلات الفرعية تتمثل في: - ما عادات وانماط استخدام مواقع التواصل الاجتماعي بولاية الاغواط ؟ - ما مدى انشار الموضوعات الدينية عبر مواقع التواصل الاجتماعي ؟ - ما مدى استخدام الامة لمواقع التواصل الاجتماعي في نشاطهم الدعوي؟ نهدف من خلال دراستنا الى التعرف على النشاط الدعوي للائمة المساجد عبر صفحات التواصل الاجتماعي واثاره على المستخدمين ، وفي دراستنا اعتمدنا على المنهج الوصفي وأداة جمع البيانات تمثلت في الاستبيان لدراسة مجتمع الدراسة المتكون من 100 فرد من مستخدمي مواقع التواصل الاجتماعي بولاية الأغواط حيث توصلنا الى النتائج التالية: 1. لكنة وطريقة المفضله لعرض المواضيع الدينية حسب افراد العينة هي طريقة فيها مشاعر واحاسيس وي تم معالجة مواضيعها بطريقة فيها الدعابة والمزاح لتجلب الناس اكثر لمتابعة والاستفادة من المواضيع الا ان بعض المواضيع لا تتحمل ذلك مثل القران الكريم والحديث النبوي الشريف. 2. التفاعل مع المنشورات الدينية عبر مواقع التواصل الاجتماعي يختلف من مستخدم الى اخر حيث انه هناك من يعجب بالمنشور الديني ويعبق عليه ويشاركه وهناك من يكفي بواحدة منهم. 3. افراد العينة يشاركون المنشورات الدينية عبر صفحاتهم بمواقع التواصل الاجتماعي من اجل عده نقاط اهمها نشر الفضيله والاخلاق الحميده للدين الاسلامي الحنيف. 4. استخدام الائمة لمواقع التواصل الاجتماعي في نشاطهم الدعوي دائم ومستمر لما وجدوه من وسائل تكنولوجيه حديثه عبر هذه المواقع ساهمت في تكبير نشاطهم الدعوي وايصاله الى اكبر قدر ممكن من المستخدمين. 5. مجموعه من افراد العينة او اكثرهم يرون ان النشاط الدعوي للائمه عبر مواقع التواصل الاجتماعي يساعد كثيرا في التقليل مع من التفاعل مع المحتوى الهابط الذي يشرح سلبياته ويقدم نصائح التخلي عنه. Study summary Our study came under the title of the advocacy activity of mosque imams through social networking pages and its effects on users - a study on a sample of social networking users Our study started from the problem: What is the impact of advocacy activity through the pages of social networking sites on its users in the state of Laghouat? The general problem of the study is divided into a set of sub-questions, as follows: - What are the habits and patterns of using social networking sites in the state of Laghouat? - What is the extent of the spread of religious topics through social networking sites? - To what extent does the nation use social networking sites in their advocacy activities? Through our study, we aim to identify the advocacy activity of the imams of mosques through social networking pages and its effects on users. : 1. An accent and the preferred method for presenting religious topics according to the sample is a method that contains feelings and feelings, and its topics are dealt with in a way that includes humor and banter to bring people more to follow and benefit from the topics, but some topics do not tolerate that, such as the Noble Qur’an and the Noble Prophet’s Hadith. 2. Interacting with religious publications on social media differs from one user to another, as there are those who like the religious publication, comment on it, and share it, and there are those who suffice with one of them. 3. Respondents share religious publications through their pages on social networking sites for several points, the most important of which is the dissemination of virtue and good morals of the true Islamic religion. 4. The imams' use of social networking sites in their advocacy activity is permanent and continuous, as they found modern technological means through these sites that contributed to enlarging their advocacy activity and reaching as many users as possible. 5. 5. A group of respondents or most of them believe that the preaching activity of the imams through social networking sites helps a lot in reducing interaction with negative content that explains its disadvantages and offers advice to abandon it.
دراسة على عينة مستخدمي مواقع التواصل الاجتماعي بولاية الأغواط